Pengaruh Lingkungan Kampus, Lingkungan Keluarga dan Pendidikan Ekonomi Keluarga Terhadap Minat Berwirausaha di FKIP Universitas PGRI Madiun - Alfarin Yogi Wardana; Novita Erliana Sari; Maretha Berlianantiya (CV. ITTC INDONESIA, 2023)
The purpose of this study is to determine the entrepreneurial interest of FKIP students of PGRI Madiun University in terms of the influence of the campus environment, family environment and family economic education. This research is expected to be a means of broadening horizons and additional reference sources as well as knowing the entrepreneurial interest of FKIP students of PGRI Madiun University empirically. This research uses a quantitative approach using numbers or scales. This study used a sample of 280 students who had taken entrepreneurship courses. The results of the study are (1) The campus environment has a positive and significant effect on the entrepreneurial interest of FKIP students of PGRI Madiun University. (2) The family environment has a positive and significant effect on the entrepreneurial interest of FKIP students of PGRI Madiun University. (3) Family economic education has a positive and significant effect on the entrepreneurial interest of FKIP students of PGRI Madiun University.